Phenotypic and functional characterisation of synovial fluid-derived neutrophils in knee osteoarthritis and knee infection - Manukyan, G; Gallo, J; Mikulkova, Z; Trajerova, M; Savara, J; Slobodova, Z; Fidler, E; Shrestha, B; Kriegova, E (Osteoarthritis and cartilage, 2023)
OBJECTIVE: An increase in the number of neutrophils (NEUs) has long been associated with infections in the knee joints; however, their impact on knee osteoarthritis (KOA) pathophysiology remains largely unexplored. DESIGN: This study compared the phenotypic and functional characteristics of synovial fluid (SF)-derived NEUs in KOA and knee infection (INF). RESULTS: KOA NEUs were characterised by a lower expression of CD11b, CD54, and CD64 and higher expression of CD62L, TLR2, and TLR4 compared with INF NEUs. Except for CCL2, lower levels of inflammatory mediators and proteases were detected in KOA SF than in INF SF. Functionally, KOA NEUs displayed increased reactive oxygen species production and phagocytic activity compared with INF NEUs. Moreover, KOA and INF NEUs differed in cell sizes, histological characteristics of the surrounding synovial tissues, and their effects on the endothelial cells assessed by human umbilical vein endothelial cells. When KOA patients were subdivided based on the SF NEU abundance, patients with high NEUs (10%-60%) were characterised by i) elevated SF protein levels of TNF-α, IL-1RA, MMP-9, sTREM-1, VILIP-1 and ii) lower CD54, CD64, TLR2 and TLR4 expression compared to patients with low NEUs (<10%). Analysis of paired SF samples suggests that low or high NEU percentages, respectively, persist throughout the course of disease. CONCLUSIONS: Our findings suggest that NEU may play a significant role in KOA pathophysiology. Further studies should explore the mechanisms that contribute to the increased number of NEUs in SF and the clinical consequences of neutrophilic phenotype in KOA.
Keywords: Knee Joint; Phenotype; fenotyp; Endothelial Cells; Low-grade inflammation; Knee osteoarthritis; Toll-Like Receptor 2; endoteliální buňky; artróza kolenních kloubů; lidé; Synovial Fluid; neutrofily; Neutrophils; Osteoarthritis, Knee; toll-like receptor 2; Immunophenotype; synoviální tekutina; Toll-Like Receptor 4; Phagocytosis; ROS; Humans; kolenní kloub; toll-like receptor 4